MASALAH-MASALAH PERKAWINAN PADA MASYARAKAT KATOLIK DI TANIMBAR – MALUKU TENGGARA BARAT - Refo, Ignasius SS.; Seralarat, Kornelis (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STPAK St. Yohanes Penginjil Ambon, 2017)
The purpose of this study is to achieve an understanding of the marital problems of Catholics that occurred in the Tanimbar in the Diocese of Amboina. In this research, we used social methods, namely qualitative research method. The reason behind this research is this method can help to describe the life of people from within, from the point of understanding of the person being studied. Thus, the result of this study present a better understanding of issues surrounding marriage and how religious view affect people, who are practicing their marital life.